Spatio-temporal dynamics of the carbonate system during macroalgae farming season in a semi-closed bay in southeast China - Zhang, Zhi; Wang, Feipeng; Lei, Lingyi; Zheng, Nan; Shen, Zhongyuan; Mu, Jingli (Frontiers in Marine Science, 2024)
Ocean Negative Carbon Emission (ONCE) involves utilizing natural marine chemistry and biology, along with mariculture, to achieve carbon sink goals. Growing awareness of the interplay between aquaculture and the coastal carbonate system has drawn researchers’ attention amid ring CO2 concentrations and the negative impacts of aquaculture on the environment. In this study, twelve sites representing different maricultural types were selected, including macroalgae, shellfish, fish, and non-farming areas. The environmental factors, dissolved inorganic carbon (DIC), total alkalinity (TA), and pCO2, were measured monthly during kelp farming periods. Nitrate is a major component of total nitrogen, and the NO3-N concentration in the macroalgal culture zone was lower than others, indicating effective nitrogen removal by macroalgae aquaculture. TA and DIC in non-farmed areas demonstrated larger variation ranges than in farming areas, probably due to the effects of precipitation on salinity. Aquaculture activities effectively maintained TA and DIC, with macroalgae cultivation playing an important role in TA stability, potentially resisting acidification. The pCO2sea-air of macroalgae culture areas in spring was slightly negative, suggesting carbon sink potential. However, further research is needed to assess the full extent of this “fourth type” of blue carbon, including accurate carbon footprint calculation and the contributions of particulate organic carbon and recalcitrant dissolved organic carbon. This study provided insight into the comprehensive contribution of different aquaculture types to the fishery environment and carbonate system, which can help guide aquaculture management and facilitate the carbon-neutral transition of aquaculture.